Clinical and Sonographic Evaluation of Postmenopausal Bleeding (PMB) Followed by Diagnostic and/or Therapeutic Hysteroscopy and Guided Biopsy in Jordanian Hospitals - Omar, Abu-Azzam (Medicina (Kaunas), 2020)
Background and Objectives: The goal of this study was to evaluate the clinical sonographic evaluation of postmenopausal bleeding (PMB) followed by diagnostic and/or therapeutic hysteroscopy and guided biopsy in Jordanian hospitals. Materials and Methods: A retrospective multi-centric study was performed in hospitals in Al-Karak and Amman from 2014–2016. The study recruited 189 cases to evaluate the aetiology of postmenopausal bleeding. Atrophic endometrium was observed as a major cause of postmenopausal bleeding according to histopathology. The cases were also distributed according to parity in which nulliparous patients were observed. Results: Hysteroscopy was observed to be effective for the diagnosis of postmenopausal bleeding. Conclusion: There is a need to assess more approaches for the diagnosis of postmenopausal bleeding among women.